The impact of COVID-19 on sport: possible future scenarios? - Urso, A. (EWF Scientific Magazine, 2020)
Reading the future, in life as well as in top sports, is generally aimed at maximum profit with minimum means. During this pandemic we have realized that such systems never provide for a second choice and how highly vulnerable they are. It is a gamble, a bet that can be lost. Risking is a ... a very risky business! What can we learn from it? One of the many things is that, since crises are always precious moments, indeed occasions for reflection: who knows if with a little common sense and reflection on more enlightened views, one cannot elaborate a different thought for the future organization of sport. Now as never before, we need thought of a higher kind.